-90(x+6)=-207

Simple and best practice solution for -90(x+6)=-207 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -90(x+6)=-207 equation:



-90(x+6)=-207
We move all terms to the left:
-90(x+6)-(-207)=0
We add all the numbers together, and all the variables
-90(x+6)+207=0
We multiply parentheses
-90x-540+207=0
We add all the numbers together, and all the variables
-90x-333=0
We move all terms containing x to the left, all other terms to the right
-90x=333
x=333/-90
x=-3+7/10

See similar equations:

| -31=-2r+7 | | s+40/9=10 | | 11z+z-2z+5z-14z=25 | | m/0.4=6 | | 91n+6+5n-31=203 | | 112+(5x-8)+(6x-12)=180 | | z/3+14=17 | | x/4-15=25 | | 13/4x22/3=x | | 12d-10d+2d+7d-10d=30 | | -8(7-9x)+54=-146 | | 7(-6x+1)=259 | | 10x4x= | | 4*x/60=1 | | 12((y+1)/(4))+5y=0 | | Y=22x-77 | | 59+(x+40)+(2x)=180 | | -5d+7d=72 | | (10z+17)+(2z+25)=180 | | 29a-13a-12a-3a=14 | | 29a-13a-12a-3a=13 | | x-37=4(2x+3)-7 | | (15x)=(540+9x) | | -7(3x-9)+15x=-33 | | 56.4.5x=110 | | 2(x-5)-29=24-5x | | 6=15-3*x | | 33n+8n+2n-24n=19 | | 33d-20d-6d+2d-6d=27 | | -5(4x+9)+13x=-87 | | 25v-21v+10v-6v=24 | | 18t=(3^7+6)+15t-(98-76) |

Equations solver categories